Hygroscopicity‐ and Size‐Resolved Measurements of Submicron Aerosol on the East Coast of the United States. Issue 3 (13th February 2018) - Phillips, B. N.; Royalty, T. M.; Dawson, K. W.; Reed, R.; Petters, M. D.; Meskhidze, N.
Abstract: Atmospheric measurements of aerosol size‐resolved hygroscopicity at submicron sizes are carried out at the United States Army Corps of Engineers Field Research Facility in Duck, North Carolina. The scientific aim of the field deployment is to gain improved understanding of the springtime advection of aerosols from the East Coast of the United States over the Atlantic and help to constrain assessments of anthropogenic particle contributions to the marine boundary layer aerosol budget. Air mass back trajectories show that the aerosol sampled at the coast is largely of continental origin that either gets transported directly from the land or spends some time over the Atlantic Ocean. Aerosol size‐resolved hygroscopicity measurements are consistent with air masses of both continental and marine background that are heavily influenced by the continental outflow. Aitken and accumulation mode mean diameters range from 49.1 ± 1.7 nm to 66.9 ± 0.8 nm and 142.8 ± 1.1 nm to 155.0 ± 2.8 nm, respectively. Hygroscopicity distributions for 96 nm, 188 nm, and 284 nm dry‐sized particles show the mode hygroscopicity parameter range from 0.20 ± 0.01 to 0.54 ± 0.03, suggesting the presence of anthropogenic aerosols. We have used the method described by Royalty et al. (2017) to decompose the hygroscopicity distributions into three distinct classes based on the ambient aerosol hygroscopic properties relative to the hygroscopic properties of a reference compound. The method shows that continental outflow heavily influences aerosol chemical and physical properties at the East Coast, with hygroscopicities of submicron aerosols consistent with sulfate‐containing species (62% to 83%), with small contributions from sodium‐ and carbon‐containing particles (up to 9% and 37%, respectively). Key Points: Continental outflow heavily influences submicron aerosol chemical and physical properties in North Carolina coastal marine boundary layer Submicron aerosols are mostly sulfate like, with small contribution from sodium‐ and carbon‐containing particles Aerosol classes derived based on hygroscopicity measurements are consistent with chemical composition data from the closest IMPROVE site